Dégradation spontanée des anthocyanes des feuilles et poudres de quelques plantes médicinales luttant contre la drépanocytose dans la ville de Kisangani. « Cas d’Annona muricata ; Justicia secunda ; Justicia tenella et Vigna inguiculata » - SINGA, Nathan IUNGBI; Amos IUNGBI SINGA,; Emmanuel YANGA EKUKA, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
The present work concerns "The spontaneous degradation of anthocyanins in the leaves and powders of some medicinal plants fighting against sickle cell disease in the city of Kisangani ". Case of Annona muricata; Justicia secunda; Justicia tenella and Vigna inguiculataThe water content for these 4 plants was determined and gave the following results for moisture: 87.40% for Annona muricata, 87.95% for Justicia secunda, 89.90 for Justicia tenella and 88.95% for Vigna ingwiculata.Then we found the following results for the dry matter: 12.60 for Annona muricata, 12.05% for Justicia secunda, 10.10% for Justicia tenella and finally 11.05% for Vigna inguiculata.Toxic ions were investigated in the different samples, apart from Justicia secunda and Vigna inguiculata, which showed the presence of oxalates and cyanides in trace, the other plants are free of toxic ions.Absorbances of the aqueous and alcoholic solutions of these plants showed that anthocyanin degradation is a function of time and gave an idea of ​​the storage time of these dry samples under ambient conditions for later use.If stored at room temperature (28 ± 2 ° C), the leaves of Annona muricata and Vigna inguiculata degrade rapidly as the powders, for against Justicia secunda and Justicia tenella are the powders that degrade rapidly than the leaves .